Pelaksanaan Sertifikasi Tanah Wakaf: (Studi Di Kabupaten Lombok Timur) - Alpian Hadi Wisastra; Arba Arba (Private Law, 2022)
This study aims to find out and understand how the enforcement of waqf land certification in East Lombok Regency. Another aims which hopefully reached by this study is the identification of what factors that become the obstacles in the waqf land certification process. The type of research used is empirical legal research with a statutory approach, conceptual approach, empirical or sociological approach. The mechanism of research used by this study within the process to determine the research sample is Random Sampling Technique. Respondents used were located in three sub-districts, with each sub-district included of five respondents so that the total number of respondents used was 15. While the total number of informants used to complete this research was six informants. Data analysis was carried out qualitatively. The results of the analysis show that firstly, the implementation of waqf land certification in East Lombok Regency has not been implemented as stated in the law. This is due to a lack of public understanding of the procedures for waqf land. Secondly, factors and obstacles in the certification process are caused by the simplification of the attitude of the community towards the importance of waqf land certification, the community also feels strong enough not to certify as long as the physical building is built on the waqf land. Seeing the implementation and obstacles above, there are several suggestions and suggestions in overcoming this, namely the need to further intensify coordination between the Office of the Ministry of Religion and the Office of the National Land Agency (BPN), in order to quickly conduct outreach and socialization to the community.